2016
DOI: 10.1371/journal.pone.0166577
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Association Mapping for Agromorphological and Grain Quality Traits of a Structured Collection of Durum Wheat Landraces Including subsp. durum, turgidum and diccocon

Abstract: Association mapping was performed for 18 agromorphological and grain quality traits in a set of 183 Spanish landraces, including subspecies durum, turgidum and dicoccon, genotyped with 749 DArT (Diversity Array Technology) markers. Large genetic and phenotypic variability was detected, being the level of diversity among the chromosomes and genomes heterogeneous, and sometimes complementary, among subspecies. Overall, 356 were monomorphic in at least one subspecies, mainly in dicoccon, and some of them coincide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 77 publications
9
34
0
Order By: Relevance
“…In previous studies of kernel traits in durum, only kernel weight-related QTLs have been identified using traditional linkage mapping and genome-wide association mapping [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. After searching QTL identified here with previously reported QTL in durum wheat genome, most of the SNPs identified from kernel-related traits in this study were close to or overlapped with the positions of kernel weight-related QTL reported in previous studies.…”
Section: Combination Analysis Of Loci Identified Here With Previouslysupporting
confidence: 62%
“…In previous studies of kernel traits in durum, only kernel weight-related QTLs have been identified using traditional linkage mapping and genome-wide association mapping [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. After searching QTL identified here with previously reported QTL in durum wheat genome, most of the SNPs identified from kernel-related traits in this study were close to or overlapped with the positions of kernel weight-related QTL reported in previous studies.…”
Section: Combination Analysis Of Loci Identified Here With Previouslysupporting
confidence: 62%
“…However, the setting of k is highly dependent on the scope of the research and here the preference was given to capturing similarities rather than divergences. A large portion of admixture among landraces remained unfixed with the set value of k , and this could justify the difference in the number of clusters between our work and that of Ruiz et al (2012). The ability to distinguish following waves of dispersion among landraces was one of our scopes and this was achieved by finding separation between the two main centers of origin/diversity (Middle East and Ethiopia) and other landraces.…”
Section: Discussionmentioning
confidence: 82%
“…In previous research, a panel of 190 Spanish durum wheat landraces was attributed to nine sub-populations (Ruiz et al, 2012), while a similar set of the germplasm collection used here, comprising 134 modern durum cultivars, was assigned to six sub-populations by Maccaferri et al (2003). In our research, the number of clusters used for stratification could have been increased, to allocate four additional sub-populations among landraces of Cluster 4.…”
Section: Discussionmentioning
confidence: 91%
“…More recently, a genomic wide association study (GWAS) has been conducted for seedling habit, together with other important agronomic traits, and significant marker-trait associations (MTAs) have been found for this trait on chromosomes 3B, 4A and 6B [21]. Significant MTAs for the prostrate/erect trait have also been identified in durum wheat: Giraldo et al [22] found two chromosome regions on 3A and 3BL, significantly associated to plant juvenile growth habit in tetraploid wheats (T. durum and T. dicoccum). In the case of barley, the close association existing between the semi-dwarfing sdw1/denso gene regulating plant height and the prostrate growth habit could be explained by the pleiotropic effect of sdw1/denso gene on tiller angle [23].…”
Section: Introductionmentioning
confidence: 99%